2003
DOI: 10.1161/01.cir.0000087606.18453.fd
|View full text |Cite
|
Sign up to set email alerts
|

Constrictive Pericarditis in 26 Patients With Histologically Normal Pericardial Thickness

Abstract: Background— Traditionally, increased pericardial thickness has been considered an essential diagnostic feature of constrictive pericarditis. Although constriction with a normal-thickness pericardium has been demonstrated clinically by noninvasive imaging, the details of clinicopathological correlates have not been described. Methods and Results— A total of 143 patients with proven constriction underwent pericardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
125
1
12

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(141 citation statements)
references
References 11 publications
3
125
1
12
Order By: Relevance
“…Constrictive pericarditis represents a hemodynamic syndrome, which is difficult to diagnose by morphological assessment of the pericardium. Recently, Talreja et al 15 demonstrated that constrictive pericarditis does not correlate with pericardial thickness, commonly used as an index of constriction. Measurements of pressure and volume signals using in vivo LV catheterization allowed us to characterize the constrictive phenotype in IFN-␥-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Constrictive pericarditis represents a hemodynamic syndrome, which is difficult to diagnose by morphological assessment of the pericardium. Recently, Talreja et al 15 demonstrated that constrictive pericarditis does not correlate with pericardial thickness, commonly used as an index of constriction. Measurements of pressure and volume signals using in vivo LV catheterization allowed us to characterize the constrictive phenotype in IFN-␥-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Chest X-ray may demonstrate pericardial calcification. Echocardiography is essential in the diagnosis of CP, but right and left heart catheterization with hemodynamic evaluation may be required to confirm the diagnosis [185][186][187] . Cardiac fibrosis develops more frequently and rapidly in CP than in other causes of right-sided heart failure, perhaps due to higher hepatic venous pressures leading to severe zone 3 congestion and necrosis [2] .…”
Section: Constrictive Pericarditis (Cp)mentioning
confidence: 99%
“…Following Cardiac surgery-11% to 37% (post-pericardiectomy-10% to 40%, previous cardiac surgery-0.3%) [10] dium are fibrosed and fused together [11], although not necessarily always thickened [12], prevent the heart from expansion and resulting in minimal ability to adapt to volume changes and significant dynamic respiratory variation in blood flow in the chambers of the heart attributed to isolation of the cardiac chambers from intrathoracic respiratory pressure changes, i.e., dissociation between intrathoracic and intracardiac pressures with enhanced ventricular interaction as reported by Hatle et al in 1989 [13].…”
Section: Most Common Less Commonmentioning
confidence: 99%